The Effect of Disclosure of Corporate Social Responsibility, Profit Quality, and Business Risk on Company Value - Cucu Hapita Pitri; Aloysius Harry Mukti (Journal of Accounting Auditing and Business, 2023)
This study aims to examine the effect of disclosure of Corporate social responsibility, earnings quality, business risk on firm value. The population in this study are all mining companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used was purposive sampling method and 53 data samples were obtained. The analytical method used is Multiple Linear Regression. The results of the study show that the disclosure of Corporate social responsibility has a positive effect on firm value, while earnings quality has no effect on firm value. As well as business risk does not affect the value of the company.